2023
DOI: 10.1097/phh.0000000000001697
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Provision of Community-Building Activities by Nonprofit Hospitals, 2010-2019

Abstract: As part of their annual tax report, nonprofit hospitals are asked to report their community-building activities (CBAs); yet, little is known to date about hospitals' spending on such activities. CBAs are activities that improve community health by addressing the upstream factors and social determinants that impact health. Using data from Internal Revenue Service Form 990 Schedule H, this study used descriptive statistics to examine trends in the provision of CBAs by nonprofit hospitals between 2010 and 2019. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The outcomes presented in our study are only representative of hospitals that reported evaluation measures in their CHNAs. Our previous research has found that hospitals reporting evaluation measures are more likely to be system members, more likely to have hired a consultant to conduct their CHNA, and less likely to be located in rural areas compared to hospitals that did not report evaluation outcomes (Yeager et al, 2023). It is important to note that in coding evaluation outcomes, we were limited to the information that hospitals include in their publicly available CHNAs/IPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcomes presented in our study are only representative of hospitals that reported evaluation measures in their CHNAs. Our previous research has found that hospitals reporting evaluation measures are more likely to be system members, more likely to have hired a consultant to conduct their CHNA, and less likely to be located in rural areas compared to hospitals that did not report evaluation outcomes (Yeager et al, 2023). It is important to note that in coding evaluation outcomes, we were limited to the information that hospitals include in their publicly available CHNAs/IPs.…”
Section: Discussionmentioning
confidence: 99%
“…See prior work for more information on the complete coding protocol development and process . The current study relies on variables that were added to the coding protocol to assess how often hospitals report evaluation outcomes in their CHNAs (Yeager et al, 2023). More specifically, the primary variable capturing evaluation data was…”
Section: Initial Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our coding strategy was developed using a previous round of community benefit documents and is reported elsewhere. 20 We coded CHNAs for the top 5 health needs identified, and then coded the top 5 health needs addressed in the corresponding IS. The coding team underwent structured training on the coding strategy, and we tested for interrater reliability with a set of 15 test documents.…”
Section: Methodsmentioning
confidence: 99%